Environmental education and ecological sensitivity shaping economics students behavior in Indonesia - Indriastuti, Mila; Wardana, Arief Budi; Safitra, Dhian Adhetiya; Sihombing, Pardomuan Robinson (Jurnal Akuntansi dan Auditing Indonesia, 2026)
This study investigates the effect of environmental education and ecological sensitivity across different institutional types to environmental behavior among economics and business students in Indonesia. Using a quantitative approach, data were collected through a 35-item questionnaire administered to 565 students from economics and business faculties at institutions under the Ministry of Education, Culture, Research, and Technology and those coordinated by other ministries or government agencies. Data were analyzed using t-tests, Structural Equation Modeling–Partial Least Squares, and Multi-Group Analysis. The findings reveal significant differences in environmental behavior across institution types and show that environmental education and ecological sensitivity positively and significantly influence students’ environmental behavior. This study extends the CADMIACA framework by integrating institutional context into the analysis of environmental behavior in Indonesia. However, the study is limited to economics and business students and relies on self-reported data. The results contribute to literature and offer implications for curriculum and policy.